The Utility of Preoperative CT Scans for the Differentiation of Mucinous versus Non-mucinous Colorectal Adenocarcinoma - Apisarnthanarak, Piyaporn; Polsak, Sirudcha; Suvannarerg, Voraparee; Rerkpichaisuth, Vilasinee; Muangsomboon, Kobkun; Teerasamit, Wanwarang; Pongpornsup, Sopa; Apisarnthanarak, Anucha (Asian Medical Journal and Alternative Medicine, 2023)
Objectives: To assess the characteristics of mucinous versus non-mucinous colorectaladenocarcinoma by preoperative computed tomography (CT) scans. Methods: A retrospective study was conducted over a 12-year, 6-month period for a comparative assessment of preoperative abdominal CT scans in 143 participants postoperatively confirmed with either mucinous (47 participants) or non-mucinous colorectal adenocarcinoma (96 participants). Two experienced abdominal radiologists separately conducted a blinded review of preoperative CT scans for tumor characterization. A stratified comparative analysis was performed. Results: The mean tumor diameter and length were significantly greater in the mucinous group (p-value < 0.001). The presence of heterogeneous enhancement and an area of hypoattenuation greater than two-thirds of the tumor volume were more frequently visualized in the mucinous group (p-value = 0.001 and p-value < 0.001, respectively). Tumor characterization as a heterogeneous enhancement plus an area of hypoattenuation more than two-thirds of the tumor volume had diagnostic utility for mucinous adenocarcinoma with a sensitivity, specificity, and accuracy of 66.0%, 95.8%, and 86.0%, respectively. Conclusions: Preoperative CT scans have potential for differentiation of mucinous versus non-mucinous colorectal adenocarcinoma.